Les vaccins dans la prévention des infections associées aux soins - Gagneux-Brunon, A. (Journal Des Anti-Infectieux, 2017)
The burden of healthcare-associated infections (HAIs) is global and major. Escherichia coli, Staphylococcus aureus, Clostridium difficile are the most frequent associated pathogens. Infection control measures are crucial but not sufficient to stem the burden of HAIs. Due to antimicrobial resistance, lack of therapeutic options for treatment of totally-drug resistant organism is also observed. Therefore, alternative strategies to antimicrobial drugs are urgently needed to prevent and treat HAI. Among these strategies, vaccines and passive immunization are probably one of the most attractive. In this review, we will discuss licensed and non-licensed vaccines for HAIs at-risk patients and HCWs to prevent HAI. The benefit of Influenza and rotavirus vaccines in patients to prevent these viral IAS is reviewed. The development of an S. aureus vaccine, previously associated to failures, seem to be complicated. These failures allow however a better knowledge of S. aureus immunity. For C. difficile, the goal of obtaining a preventive vaccine seems to be near. Development of vaccines to prevent gram negative bacteria involved in IAS remain challenging and confined in early phases of development. Vaccination of at risk patients is however challenging due to the poor immune response to vaccines usually obtained. Therefore, immunization of healthcare workers (HCWs) is crucial to prevent IAS as it is associated to herd immunity. We also review here the benefit of HCWs immunization against measles, pertussis, influenza, varicella and hepatitis B to prevent HAIs.